2023
DOI: 10.3390/ijerph20032472
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Facebook on Social Support and Emotional Wellbeing in Perinatal Women during Three Waves of the COVID-19 Pandemic in Mexico: A Descriptive Qualitative Study

Abstract: The COVID-19 pandemic affected the mental health of pregnant and postpartum women in unique, unprecedented ways. Given the impossibility of delivering face-to-face care, digital platforms emerged as a first-line solution to provide emotional support. This qualitative study sought to examine the role that a closed Facebook group (CFG) played in providing social support for Mexican perinatal women and to explore the concerns they shared during the COVID-19 pandemic. A thematic analysis of all the posts in the CF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Of the 20 studies using thematic analysis, 16 (80.0%) [ 38 , 49 , 50 , 53 , 65 , 78 , 90 , 91 , 113 , 122 , 127 , 134 , 140 , 145 , 150 , 163 ] used thematic analysis to analyze the content features of online information and extract topics. In addition, Oren et al [ 55 ] used grounded theory–based thematic analysis to examine qualitative data to determine the topic of tweets shared during the COVID-19 outbreak.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 20 studies using thematic analysis, 16 (80.0%) [ 38 , 49 , 50 , 53 , 65 , 78 , 90 , 91 , 113 , 122 , 127 , 134 , 140 , 145 , 150 , 163 ] used thematic analysis to analyze the content features of online information and extract topics. In addition, Oren et al [ 55 ] used grounded theory–based thematic analysis to examine qualitative data to determine the topic of tweets shared during the COVID-19 outbreak.…”
Section: Resultsmentioning
confidence: 99%
“…The usefulness of social media as an information tool for health and disease prevention has also been reported [30][31][32]. Public institutions and academic institutions, such as the WHO, CDC, National Institute of Health (NIH), universities, and the Ministry of Health, Labour, and Welfare have opened official social media accounts and are actively disseminating information.…”
Section: Discussionmentioning
confidence: 99%
“…This advantage is being used to attempt various forms of support for pregnant women. In particular, the use of social media for mental health support for pregnant women has been reported to be effective [31,32]. For many people, social media has the advantage of being easy and casual to use, so it will be necessary to effectively utilize social media.…”
Section: Discussionmentioning
confidence: 99%
“…The data available in this country show that, during the COVID-19 health crisis, pregnant adults suffered stress (32%) and depression (17.5%; Medina-Jimenez et al, 2022), greater stress was associated with higher levels of depression and social support was associated with less depression (Rivera-Rivera et al, 2021). Likewise, it was observed that experiencing pregnancy and postpartum during the pandemic was overwhelming due to the intense fear of contagion and the multiple demanding situations (Lara et al, 2023). Having data on the effects of the COVID-19 pandemic on the mental health and well-being of postpartum adolescent mothers will fill a gap in research, both in Mexico and in other countries, and serve as the basis for PPD prevention and management in this population in future crises.…”
Section: Introductionmentioning
confidence: 94%